Ammonia removal from chicken manure digestate through vapor pressure membrane contactor (VPMC) and phytoremediation - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Ammonia removal from synthetic ammonia solutions and chicken manure digestate via vapor pressure membrane contactor through Polytetrafluoroethylene (PTFE) membrane was investigated. The highest ammonia mass flux, separation factor, and removal efficiencies of 28.6 0.2 g N/m(2) h, 53.9 +/- 10.7, and 97.6 +/- 0.7% were observed for synthetic solutions, respectively. Ammonia removal efficiency of 93.6 +/- 1.9% through membrane contactor was observed for chicken manure digestate decreasing the total ammonia concentration from 3643.5 +/- 67.2 to 230.9 +/- 46.2 mg N/L. Phytoremediation via Lemna minor species was used as a polishing step to remove remaining ammonia from the membrane contactor effluent. Total ammonia concentration was then decreased below 2 mg N/L through evaporation, nitrification, and plant uptake processes occurring in the phytoremediation containers. This study reveals that ammonia can be successfully removed via VPMC and phytoremediation systems and the process is implementable as it can be coupled to anaerobic digestion processes to recover ammonia and to prevent ammonia inhibition. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Ammonia removal; Aquatic macrophyte; Membrane; Poultry waste; Recovery; VOLATILE FATTY-ACIDS; WASTE-WATER STREAMS; ANAEROBIC-DIGESTION; NUTRIENT RECOVERY; POULTRY LITTER; CO-DIGESTION; DUCKWEED; INHIBITION; NITROGEN; BIOMASS